“A Song of Ice and Fire” in Historical Perspective: a Mimetic Study - Haryadi, Rofiq Noorman; Putra, Rizky Maulana; Poetri, Maharanny Setiawan; Sunarsi, Denok; Mulyadi, Mulyadi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
Medieval England was filled with history such as invasions by foreigners, The Wars of the Roses, and power struggles. A Song of Ice and Fire is a historical fiction novel that have a lot of in common with Medieval England. The aim of this study is to find the similarities between the novel and real medieval England in terms of Setting, Event, and the similarities within each of Character. The author uses the Qualitative Research with Mimetic approach by Abrams. The authors found that there are several similarities in terms of Setting between the novel and the real world, one of them is the geographical condition between two countries, Westeros and England. The Event in the story also resembles the historical event such as Aegon Conquest that resembles William Conquest in 1066, And the Characters also brought the same attribute that resembles the original actors in medieval England.